ANALISIS KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI (Studi Empiris Pada Perusahaan Sub Sektor Perindustrian Yang Terdaftar Di Bursa Effek Indonesia Tahun 2017-2022) - Utami, Fardiyati Diyah; Margie, Lyandra Aisyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to test and obtain empirical evidence regarding the effect of dividend policy and investment decisions on firm value with good corporate governance as a moderating variable in the object of industrial sub-sector companies listed on the IDX in 2017-2022. This type of research is quantitative which is processed with the help of E-views with the moderating regression analysis (MRA) method. The results showed that the Investment Decision variable had a persial effect on Firm Value. While Dividend Policy has no effect on Company Value. Good Corporate Governance (GCG) is able to moderate the relationship of Investment Decisions on Company Value, while Good Corporate Governance is unable to moderate the relationship of Dividend Policy on Company Value.